Introduction to Cybersecurity in the Internet of Things - Gai, Keke; Yu, Jing, 1989-; Zhu, Liehuang (Boca Raton : CRC Press, 2024)
"This book addresses the security challenges facing the rapidly growing Internet of Things (IoT) industry, including the potential threats and risks arising from its complex architecture. The authors discuss the overall IoT architecture, covering networking, computing, security threats and risks to hardware such as sensors, actuators, portable devices, etc., and infrastructure layers. They cover a range of technical concepts such as cryptography, distributed storage and data transmission, and offer practical advice on implementing security solutions such as authentication and access control. By exploring the future of cybersecurity in the IoT industry, with insights into the importance of big data and the threats posed by data mining techniques, this book is an essential resource for anyone interested in or working in the rapidly evolving field of IoT security"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Internet of things -- Security measures; Computer security